GENDER DIFFERENCES IN MULTIPLE INTELLIGENCES AMONG SECONDARY SCHOOL STUDENTS: A COMPARATIVE STUDY - Panchal, Jetal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examined gender differences in multiple intelligences among secondary school students. 400 students (200 males, 200 females) studying in standard IX and X from Gujarati medium secondary schools of urban and rural areas of Central Gujarat were selected by a stratified random sampling method, out of which 200 students were from urban areas and 200 students were from rural areas. The present study employed the descriptive survey method to collect data. A Multiple Intelligences Assessment Scale (MIAS) (80 items, 3-point Likert scale), based on Gardner’s theory, was constructed and standardized by the researcher as a data collection tool to assess the multiple intelligences of secondary school students. The MIAS showed high reliability and validity. The t-test was used for the analysis of data. Results revealed significant gender differences in five intelligence types. Female students demonstrated significantly higher levels of linguistic, logical-mathematical, interpersonal, and intrapersonal intelligences compared to male students. Conversely, male students exhibited significantly higher naturalist intelligence. No significant gender differences were found in spatial, bodily-kinesthetic, and musical intelligences. These findings partially support some earlier studies but contradict others, demonstrating that cultural and contextual influences may shape different intelligence types. Schools should focus on specialized teaching approaches to improve males' language, math, social skills, and self-awareness, as well as girls' nature awareness. The study suggests multiple intelligences-based instruction, specialized teacher and student workshops, and field visits to build naturalist intelligence. This research helps educators, parents, and educational administrators recognize and foster secondary school students' unique intellectual strengths.